Pengaruh Pemberian Teknik Hypnobreastfeeding Terhadap Motivasi Ibu Dalam Memberikan ASI Eksklusif di Wilayah Kerja Puskesmas Air Itam Tahun 2023 - Ayudita Ayudita; Tania Litizha (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Only half of the 2.3 million infants under six months old in Indonesia receive exclusive breastfeeding. Hypnobreastfeeding is a relaxation technique that facilitates the breastfeeding process holistically, addressing the mind, body, and soul of the breastfeeding mother. The aim of this study is to review 'The Effect of Hypnobreastfeeding Techniques on Mothers' Motivation to Provide Exclusive Breastfeeding.' This research is a Quasi-Experimental study with a One-Group Pretest-Posttest design. The sample in this study consisted of 15 respondents selected using the Probability Sampling technique. The data type in this research is primary data, measured using a checklist for observation and a questionnaire given to respondents. The data were analyzed using the Wilcoxon Matched Pairs Test. The test value using the Wilcoxon test showed a Z value of -3.428 and a significance of 0.001 (p-value < 0.05), indicating that there is an effect of the Hypnobreastfeeding technique in increasing mothers' motivation to provide exclusive breastfeeding. It is recommended that healthcare workers, especially midwives, pay more attention to the condition of postpartum mothers experiencing insufficient breast milk production and suggest hypnobreastfeeding therapy to breastfeeding mothers